Starvation affects the intestinal oxidative stress, autophagy, microbiota and histology of Chinese soft-shelled turtle (Pelodiscus sinensis) - Xueying Shi; Da Yue; Qingqing Guo; Xiangce Li; Peiyu Zhang; Haiyan Liu (Aquaculture Reports)
Chinese soft-shelled turtle (Pelodiscus sinensis) frequently encounters period of starvation during its life cycle, but the impact of starvation on its intestinal physiology remains unclear. This study investigated the effects of starvation on the antioxidant status, autophagy, microflora, and histological structure in the intestinal of P. sinensis. Turtles were subjected to starvation for 1, 4, 8, 16, and 32 days (referred to as S1, S4, S8, S16, and S32). The results of histological examination showed a progressive shortening of intestine villus and thickening of the muscle layer as starvation duration increased. The ROS and MDA contents showed a gradual increase with the prolonged starvation. The activities of SOD and GPx were significantly elevated after 16 and 32 days of starvation. Transmission electron microscopy revealed the presence of autophagosomes starting from S4, with a significant increase observed after 8 days of starvation. The mRNA expression levels of autophagy-related genes (atg5, atg12, p53, p62, and lc3) were significantly upregulated with the prolonged starvation, while the expressions of mtor1 and s6k1 were significantly decreased in S32 group. Moreover, microbiota analysis via 16S rRNA sequencing demonstrated a distinct separation between the S1 group and the starving groups. Starvation led to an increase in intestinal microbial diversity, as evidenced by an elevated Shannon index and a decreased Simpson index. At the phylum level, the abundance of Firmicutes decreased, whereas Bacteroidota and Proteobacteria increased with prolonged starvation. A Mantel test showed that the abundance of Proteobacteria was significantly positively correlated to ROS contents and the expression levels of p53. In conclusion, this study suggests that starvation induce the oxidative stress and autophagy, change the structure of microbiota and morphology in the gut of P. sinensis, and provides valuable insights to the adaptive mechanisms of this species.